THE ARTISTIC CONCEPT OF SIN IN BOHDAN TOMENCHUK’S POETRY (on the base of a book “The season of non-writing poems”) - Деркачова, О. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The problem of definition of the concept and artistic concept “sin” is throughlighted in the article. The concept “sin” in moral-ethical, religious and mythological paradigm is analysed. Specify of the meaning of the sin in modern society is determined. The concept “sin” in B. Tomenchuk’s poetry is possible to exam in moral-ethical paradigm. The poet showed the changes of valuable vectors in the society which accepts as the sin the sacral being.